Multisensor Systems by Electrochemical Nanowire Assembly for the Analysis of Aqueous Solutions - Nikolaev, Konstantin G.; Ermolenko, Yury E.; Offenhäusser, Andreas; Ermakov, Sergey S.; Mourzina, Yulia G. (Frontiers in Chemistry, 2018)
The development of electrochemical multisensor systems is driven by the need for fast, miniature, inexpensive, analytical devices and advanced interdisciplinary based on both chemometric and (nano)material approaches. A multicomponent analysis of complex mixtures in environmental and technological monitoring, biological samples, and cell culture requires chip-based multisensor systems with high-stability sensors. In this paper, we describe the development, characterization, and applications of chip-based nanoelectrochemical sensor arrays prepared by the directed electrochemical nanowire assembly (DENA) of noble metals and metal alloys to analyze aqueous solutions. The transducer function of metal nanowire (NW) electrodes is synergetically combined with their electrochemical catalytic activity with respect to analytes. We demonstrate that this technique can be employed for metals (Pd, Au) and bimetallic compositions (Pd, Ni, Au) to create various multicomponent sensor nanomaterials on a single chip without the use of multistep lithography for the spatially resolved analysis of solutions. For multi-analyte sensing applications, two or more nanowires of various compositions can be individually addressed when used in liquid media, meaning that the particular surface properties of the individual nanoarray elements can be used for the electrochemical analysis of specific analytes. To demonstrate the application of a new electrochemical multisensor platform, Pd-Au, Pd-Ni, Pd, and Au NW electrode arrays on a single chip were employed for the non-enzymatic analysis of hydrogen peroxide, glucose, and ethanol. The analytes are determined at low absolute values of the detection potentials with linear concentration ranges of 1.0×10-6 - 1.0×10-3 M (H2O2), 1.5×10-7 - 2.0×10-3 M (glucose), and 0.7×10-3 - 3.0×10-2 M (ethanol), detection limits of 2×10-7 M (H2O2), 4×10-8 M (glucose), and 5.2×10-4 M (ethanol), and sensitivities of 18 µA M-1 (H2O2), 178 µA M-1 (glucose), and 28 µA M-1 (ethanol), respectively. The sensors demonstrate a high level of stability due to the non-enzymatic detection mode. Using various DENA-grown NW compositions on a single chip, we propose a novel multisensor platform, which is promising for acquiring complex analytical signals for advanced data processing with chemometric techniques aimed at the development of electronic tongue-type multisensor systems for flexible multi-analyte monitoring and healthcare applications.